Efficacy of Proximal Resin Infiltration on Caries Inhibition: Results from a 3-Year Randomized Controlled Clinical Trial. (December 2019) - Peters, M.C.; Hopkins, A.R.; Zhu, L.; Yu, Q.
This study reports 3-y outcomes of a split-mouth randomized clinical trial. Resin infiltration's capacity to arrest caries lesion progression in noncavitated proximal lesions is affirmed. Forty-two consented young adults, blinded to tooth surface allocation, were treated with resin infiltration on 1 randomly selected surface and concurrently experienced a mock infiltration procedure on another. Both treatments were provided as an adjunct to the currently accepted standard-of-care regimen (periodic prophylaxis and serial fluoride varnish applications) appropriate for the management of high caries risk. Challenging periods of low oral hygiene compliance were expected. The primary outcome measure was 3-y radiographic lesion progression. Blinded investigators evaluated each study surface for lesion progression with a series of images obtained at intervals over the 3-y course of study. Proportions of progressing lesions were compared with McNemar's test. Twenty-nine noncavitated lesion pairs in permanent posterior teeth demonstrating caries penetrating into inner enamel or outer dentin were included in the analyses. No adverse events were reported. Radiographic progression was recorded in 4 of 29 infiltrated lesions (14%) and 14 of 29 control lesions (48%, P < .003). Adjunct resin infiltration demonstrated a high 3-y efficacy of 71% (relative risk reduction). The prevented fraction was 86% for infiltration versus 52% for controls. Resin infiltration was 100% successful in arresting caries progression in inner enamel lesions (E2) and 64% in outer dentin lesions (D1). Supplementary microinvasive resin infiltration is significantly more efficacious in reducing proximal lesion progression than management by standard noninvasive therapy alone. Long-term results may shed light on whether this represents the arrest or delay of the caries disease process (ClinicalTrials.gov NCT01584024).